2005
DOI: 10.1161/01.str.0000158925.12740.87
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control and Risk of Stroke

Abstract: Background and Purpose-Adequate control of blood pressure (BP) is a cornerstone in stroke prevention. This study explored the risk of stroke in relation to the quality of BP control in a population-based cohort and whether control of hypertension was related to background characteristics of patients. Methods-A total of 27 936 subjects (10 953 men and 16 983 women), 45 to 73 years old, living in Malmö, Sweden participated in the study. Incidence of stroke was followed-up for a mean period of 6 years. Controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 25 publications
5
37
0
Order By: Relevance
“…10 Subjects were categorized into current smokers or non-smokers. Alcohol intake was assessed by a diet method previously described in detail 11 and categorized according to daily consumption.…”
Section: Baseline Examinationsmentioning
confidence: 99%
“…10 Subjects were categorized into current smokers or non-smokers. Alcohol intake was assessed by a diet method previously described in detail 11 and categorized according to daily consumption.…”
Section: Baseline Examinationsmentioning
confidence: 99%
“…We have chosen spontaneously hypertensive rats because they have clinically relevant risk factors for ischemic stroke. 11 We used immunohistochemistry (IHC), western blot, confocal microscopy, and dynamic contrast-enhanced magnetic resonance imaging (MRI) to characterize the role of pericytes, astrocytes, and endothelial cells in the remodeling of TJPs and BBB integration. We determined the spatiotemporal involvement of MMP-2 and -3 in the remodeling of TJPs in the BBB and migration of new vessels.…”
Section: Introductionmentioning
confidence: 99%
“…22 The stroma study demonstrated that among the treated hypertensive patients, 11.8% did not reach the target BP (o140/90 mm Hg), and 67% had monotherapy. 23 There was a significant correlation between the number of antihypertensives prescribed and the efficacy of lowering BP. 24 In the I-HAT study, a combination of more than two antihypertensive drugs was prescribed in more than 60% of hypertensive patients to achieve the target office Ibaraki Hypertension Assessment Trial (I-HAT) studyBP.…”
Section: Ibaraki Hypertension Assessment Trial (I-hat) Studymentioning
confidence: 99%